Studi Eksperimental Karakteristik Sifat Mmpu Basah Material Karbon Aktif Bambu Betung Sebagai Material Pad Sistem Direct Evaporative Cooling - Kinalsal Ginting, Roy; Wijaksana, Hendra; Astawa, Ketut (Teknik Desain Mekanika; Vol 10 No 4 (2021): Oktober 2021 : Teknik Desain Mekanika, 2021)
Abstract Cooling system Air Conditioning (AC) Compressor-based is one of the biggest contributors to global warming at this time. Where this system requires a large amount of energi in its use and requires freon (R-22) as refrigerant which is one of the causes of damage to the ozone layer. Based on this, a cooling system that is energi efficient and friendly to the environment is needed. One of them is the system direct evaporative cooling. Where in this system only requires two natural energies as the driving force, namely air and water. This system utilizes the process of evaporation of water on the surface of the pad material which will provide a cooling effect on the supply air (air to be cooled/outside air). This research was conducted to analyze the wettability of bamboo betung activated carbon as a material for direct evaporative cooling system. The carbonization temperatures to be used are 500oC, 600oC, 700oC, and 800oC. The activation temperature used is 600 o C with a holding time of 60 minutes. From this study, the results of specimens ACRB 500 HT60 has the highest wet formability with contact angle 20,195 o and ACRB 600 HT60 has properties capable lowest wet withcontact angle 30.972o Keywords:Carbonization,Activation,BambooBetung, Materials, Wettability, Contact Angle.